2013
DOI: 10.3329/medtoday.v25i1.16069
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of Tuberculous Meningitis Patients : Study of 30 Cases

Abstract: Tuberculosis is creating immense adverse social and economic burden in Bangladesh. Tuberculous Meningitis results from the haematogenous spread of primary or postprimary pulmonary disease or from the rupture of a subependymal tubercle into the subarachnoid space. Infection of the CNS is one of the most devastating clinical manifestations of tuberculosis This study aimed to see the presentation of tuberculous meningitis patients in tertiary level hospital of Bangladesh. This cross sectional study was carried ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
(5 reference statements)
7
3
0
Order By: Relevance
“…12 In our study there 52% of the patients were male which was in concordance with the sex distribution in the study done by Sarkar D.N. Hossain MI et al 13 Almost all (94%) TBM patients had fever and most (66%) of them had headache and vomiting, which are very pathognomonic features of meningeal irritation/infection (Table 2). Findings are comparable to the study conducted by Sharma et al and Archana Aher et al In the present study it was shown that 66% patients had meningeal sign which was to some extent corroborative to the study done by Sarkar D.N.…”
Section: Discussionsupporting
confidence: 89%
“…12 In our study there 52% of the patients were male which was in concordance with the sex distribution in the study done by Sarkar D.N. Hossain MI et al 13 Almost all (94%) TBM patients had fever and most (66%) of them had headache and vomiting, which are very pathognomonic features of meningeal irritation/infection (Table 2). Findings are comparable to the study conducted by Sharma et al and Archana Aher et al In the present study it was shown that 66% patients had meningeal sign which was to some extent corroborative to the study done by Sarkar D.N.…”
Section: Discussionsupporting
confidence: 89%
“…This may be difficult to replicate outside a dedicated research setting due to the work burden in public health laboratories of resource-limited countries like ours 31 . Similar to our finding Sarkar et al, (2013) also observed 100% negative smear microscopy 24 .…”
Section: Diagnostic Methods By Csf Analysissupporting
confidence: 92%
“…Seizures of generalized tonic and clonic type were noted 15% of our cases while reported 8.3% in Sarkar et al, (2013) 26 . The signs of meningeal irritation was present as neck rigidity or as Kernig's sign in 100% cases while cranial nerve palsies were observed in 43% of the cases, which is consistent with the other study from Bangladesh (42.5%) (Sarkar et al, 2013) but slightly lower than that of Indian study (Khatua et al, 1961) where it was 50% ). In the present study, the incidence of papilloedema was 40%.…”
Section: Diagnostic Methods By Csf Analysissupporting
confidence: 89%
See 2 more Smart Citations